Exploring Sustainable Tax Policy in Türkiye: A Qualitative Analysis of Corporate and Public Discourse in the Energy Sector - Kazan, Gülçin; Kocamış, Tuğçe Uzun; Kazan, Gülçin (Virtus Interpress, 2026)
This article examines the effect of sustainable taxation policies on public policy and institutional strategies for energy in Türkiye. The methodology of the study was to analyze the activity, sustainability, and integrated reports of a select number (10) of energy companies listed in the Borsa Istanbul (BIST) Sustainability Index over the period of 2021–2023 and to include relevant documents from public institutions in the qualitative content analysis. To complete the code creation process, the literature review and policy document analysis were categorized thematically. These categories included border carbon adjustment mechanism [BCAM] (sinirda karbon düzenleme mekanizmasi [SKDM]), carbon taxes, green finance tools, and tax incentives, which were the main themes identified through the thematic analysis. Through the analysis, it was evident that while businesses have not yet implemented the carbon tax model as an intentional strategy, they have made investments in renewable energy, energy-efficient practices, and received government incentives. Therefore, due to the ambiguity of carbon pricing instruments, there is considerable uncertainty regarding their implementation and significant institutional disparities in reporting such instruments, which create obstacles to the sector’s transformation. This article contributes to showing how removing uncertainties about carbon pricing, clearly defining incentives, and enhancing the capacity of sustainable finance contribute to the green transformation process in the case of Türkiye. These findings are also supported by the literature (Aydın, 2018; Bakış et al., 2022).
Keywords: Energy Sector; Carbon Tax; Sustainability; Green Finance; Emissions Trading System; Renewable Energy